Nilai-Nilai Perjuangan Pendidikan Karakter Islam K.H. Abdullah Sa’id - Hilalludin Hilalludin; Adi Haironi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The concept of Islamic education according to K.H. Abdullah Sa'id aims to shape individuals according to the vision of his creation as abid and caliph of Allah. He emphasized two main steps: developing a philosophical view of